Gap and Risk Analysis of Bring Your Own Device (BYOD) Usage from the Perspectives of Employee Performance, Process, and Technology at PT Sinergi Teknoglobal Perkasa - Syukma Hidayat; I Dewa Ketut Kerta Widana (Dinasti Publisher, 2026)
An analysis to examine the influence of security perceptions, technical support, and job type on employee productivity in implementing the Bring Your Own Device (BYOD) policy. This research uses a quantitative approach by distributing questionnaires to 100 employees at PT Sinergi Reknoglobal Persaka. The regression analysis results show that the three independent variables significantly affect employee productivity. High perceived security, adequate technical support, and the type of work that is compatible with the use of personal devices contribute to increased productivity. This study concludes that the implementation of BYOD policies can effectively increase employee productivity if supported by supporting factors such as data security, technical support, and job suitability. The results of this study provide important implications for companies that want to implement BYOD policies